(untitled) (European Journal of Pure and Applied Mathematics, 2015)
In the present work we define a p-adic analogue of the classicalbeta function by using Y. Morita’s p-adic gamma function. Weobtain some elementary properties of the p-adic beta function. Wegive some relations between the classical beta and the p-adic betafunctions at the values of natural numbers.